Peran Komunikasi Penerimaan Aktif dalam Membangun Kerja Sama Tim dalam Organisasi - Agis Nur Fazhan Sulistira; Puspa Isya Qoblia; Tiara Syaumi Rizki (Yayasan Lentera Avanya Nagari, 2023)
This study aims to analyze the role of active acceptance communication in building teamwork in organizations, with a focus on Karang Taruna Bhina Bakti. The research approach used is a qualitative method using in-depth interviews. Respondents who were involved in this study were members of the Bhina Bakti Youth Organization. Interviews were conducted using an interview guide designed to collect data on respondents' perceptions of active acceptance communication and teamwork. The data collected includes information about gender, age, last education, previous experience working in a team, as well as their perceptions of active acceptance communication and teamwork. The results of the study show that active acceptance communication is very important and effective in strengthening teamwork. Karang Taruna Bhina Bakti considers active acceptance communication as a factor that strengthens, increases understanding, and enhances cooperation between team members. The results of this study are expected to provide guidance for the Bhina Bakti Youth Organization in improving teamwork through more effective and inclusive communication.